GAMBARAN KEPATUHAN PERAWAT DALAM PENERAPAN CUCI TANGAN YANG BENAR DI INSTALASI RAWAT INAP RUMAH SAKIT PARINDU - Sinaga, Saur Mian; Rosanti, Yosefina; Prasetyo, Yunus Adhy (Institut Kesehatan Immanuel, 2025)
Nurses play an important role in the transmission of nosocomial infections that occur in health care facilities, hand hygiene is a standard precaution, therefore nurse compliance in applying the correct steps and indications is guided by the SOP, hand hygiene that is carried out correctly and appropriately is one way to break the chain of transmission of nosocomial infections and an indicator of the quality value of a healthcare facility. The occurrence of hand washing non-compliance by nurses can be caused by several factors such as age, gender, education and length of service.The purpose of this study was to identify the description of nurse compliance in the application of hand washing properly in the inpatient installation of Parindu Hospital. The research place is the entire room in the Parindu Hospital inpatient installation, the research instrument uses an observation sheet according to the hand hygiene SOP and Five moments at Parindu Hospital.The results of the research found by researchers during the study by observing 27 respondents who served as nurses at Parindu Hospital who obediently washed their hands properly 17 respondents (63%) while 10 respondents (37%) did not wash their hands according to the SOP. Nurse compliance with the implementation of hand washing hygiene and five moments in the Parindu Hospital inpatient installation is 63% of the 27 respondents. It is recommended that the Parindu hospital continue to conduct socialization and supervision of the implementation of hand washing compliance and five moments according to the SOP.